Association of Bactericera cockerelli (Hemiptera: Triozidae) With the Perennial Weed Physalis longifolia (Solanales: Solanaceae) in the Potato-Growing Regions of Western Idaho. Issue 6 (3rd August 2021) - Reyes Corral, Cesar A; Cooper, W Rodney; Horton, David; Miliczky, Eugene; Riebe, Jennifer; Waters, Timothy; Wildung, Mark; Karasev, Alexander V
Abstract: The potato psyllid, Bactericera cockerelli (Šulc), is a major pest of potato (Solanales: Solanaceae) as a vector of ' Candidatus Liberibacter solanacearum' (Lso). Bactericera cockerelli colonizes potato from noncrop host plants, yet we do not yet know which noncrop species are the primary sources of Lso-infected psyllids. The perennial weed, Physalis longifolia Nutt., is a high-quality host for B. cockerelli and Lso under laboratory conditions but has been overlooked in recent field studies as a source of Lso-infected psyllids. Our current study had four objectives: 1) determine whether P. longifolia is abundant in potato-growing regions of Washington and Idaho, 2) determine whether stands of P. longifolia harbor B. cockerelli and Lso, 3) identify the psyllid haplotypes occurring on P. longifolia, and 4) use molecular gut content analysis to infer which plant species the psyllids had previously fed upon prior to their capture from P. longifolia . Online herbaria and field searches revealed that P. longifolia is abundant in western Idaho and is present at low densities in the Columbia Basin of Washington. Over 200 psyllids were collected from P. longifolia stands in 2018 and 2019, confirming that B. cockerelli colonizes stands of this plant. Gut content analysis indicated that a proportion of B. cockerelli collected from P. longifolia had arrived there from potato. Confirmation that P. longifolia is abundant in certain potato-growing regions of the Pacific Northwest, and that B. cockerelli readily uses this plant, could improve models to predict the risk of future psyllid and Lso outbreaks.